WRF-Chem simulation of aerosol seasonal variability in the San Joaquin Valley - L. Wu; H. Su; O. V. Kalashnikova; J. H. Jiang; C. Zhao; M. J. Garay; J. R. Campbell; N. Yu (Atmospheric Chemistry and Physics, 2017)
WRF-Chem simulations of aerosol seasonal variability in the San Joaquin Valley (SJV), California, are evaluated by satellite and in situ observations. Results show that the WRF-Chem model successfully captures the distribution and magnitude of and variation in SJV aerosols during the cold season. However, aerosols are not well represented in the warm season. Aerosol simulations in urban areas during the cold season are sensitive to model horizontal resolution, with better simulations at 4 km resolution than at 20 km resolution, mainly due to inhomogeneous distribution of anthropogenic emissions and precipitation that is represented better in the 4 km simulation. In rural areas, the model sensitivity to grid size is rather small. Our observational analysis reveals that dust is a primary contributor to aerosols in the SJV, especially during the warm season. Aerosol simulations in the warm season are sensitive to the parameterization of dust emission in WRF-Chem. The GOCART (Goddard Global Ozone Chemistry Aerosol Radiation and Transport) dust scheme produces very little dust in the SJV, while the DUSTRAN (DUST TRANsport model) scheme overestimates dust emission. Vertical mixing of aerosols is not adequately represented in the model based on CALIPSO (Cloud-Aerosol Lidar and Infrared pathfinder Satellite Observation) aerosol extinction profiles. Improved representation of dust emission and vertical mixing in the boundary layer is needed for better simulations of aerosols during the warm season in the SJV.